Quaternary ammonium salt catalyst, and synthetic method and application of environment-friendly hydroxyalkyl acrylate capable of being directly used for synthesizing polycarboxylic concrete admixture

The quaternary ammonium catalyst prepared by the reaction of hexamethylenetetramine and ethylene iodine solves the problems of slow reaction speed and harmful substances in the synthesis of traditional hydroxyalkyl acrylates, and achieves efficient and environmentally friendly hydroxyalkyl acrylate synthesis , directly used in polycarboxylic acid-based concrete admixtures, improving production efficiency and product performance.

CN119119059AActive Publication Date: 2024-12-13ANHUI CONCH MATERIAL TECHNOLOGY CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411178697.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-13
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The traditional hydroxyalkyl acrylate synthesis method has problems such as slow reaction speed, low conversion rate, and subsequent purification and treatment are required. The product may contain harmful substances, affecting the environment and product performance.

Method used

The quaternary ammonium salt catalyst is prepared by reaction of hexamethylenetetramine and iodoethylene. It is used for the synthesis of hydroxyalkyl acrylate. It has high catalytic efficiency and good selectivity. It does not require subsequent purification and is directly used for polycarboxylic acid-based concrete admixtures. synthesis.

Benefits of technology

It realizes efficient and environmentally friendly hydroxyalkyl acrylate synthesis, reduces production costs, improves production efficiency, ensures product quality and performance, and avoids heavy metal pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119059A_ABST
    Figure CN119119059A_ABST
Patent Text Reader

Abstract

The invention provides a quaternary ammonium salt catalyst, and an environment-friendly synthetic method and application of hydroxyalkyl acrylate capable of being directly used for synthesizing a polycarboxylic acid concrete admixture. Quaternary ammonium salt synthesized by ethylene iodide and hexamethylenetetramine is used as a catalyst and is mixed with a polymerization inhibitor and acrylic acid, and under the protective atmosphere and under the heating and pressurizing conditions, the hydroxyalkyl acrylate is synthesized into the polycarboxylic acid concrete admixture. The method has the advantages of high reaction speed, high conversion rate and no need of subsequent purification treatment, and can be directly used for synthesis of concrete admixtures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material preparation, and in particular relates to a quaternary ammonium salt catalyst, a synthesis method and application of environmentally friendly hydroxyalkyl acrylate that can be directly used for the synthesis of polycarboxylic acid series concrete admixtures. Background Art

[0002] Hydroxyalkyl acrylate is an important organic compound with extremely active properties and a wide range of applications. It is mainly used in fiber processing, coatings, light-curing resins, adhesives, paper processing, rubber industry, etc. Hydroxyalkyl acrylate also plays a key role in the synthesis of polycarboxylic acid concrete admixtures.

[0003] As an important substance for improving the performance of concrete, concrete admixtures are widely used in construction projects. As an important raw material for polycarboxylic acid concrete admixtures, the synthesis method of hydroxyalkyl acrylate has always been a hot topic of research. However, traditional synthesis methods usually have problems such as slow reaction speed, low conversion rate, and the need for subsequent purification, which not only increases production costs, but also affects product performance and application effects. In addition, the product may contain harmful substances such as chloride ions and heavy metal ions, which pollute the environment.

[0004] At present, the routes for synthesizing hydroxyalkyl acrylates mainly include the ring-opening method (divided into direct method and indirect method), direct esterification method, ester exchange method, reaction method of diols and acryloyl chloride, reaction method of diol carbonate and acrylic acid, chlorohydrin method, etc.

[0005] The indirect method of ring opening of alkylene oxide and the transesterification method for producing hydroxyalkyl acrylate have many steps, which increase the production cost and are uneconomical. The reaction activity of the diol and acryloyl chloride reaction method is high and the reaction speed is fast, but the cost of acyl chloride is much higher than that of the corresponding carboxylic acid, so its application in industry is very limited. The reaction time of the diol carbonate and acrylic acid reaction method is long and the reaction temperature is high. The long-term high temperature will produce more side reactions, thereby reducing the yield. The chlorohydrin method has a long synthesis cycle, unstable product quality, and there are problems with the filtration of the byproduct NaCl and the disadvantages of high toxicity of chlorohydrin.

[0006] Consider the cost and yield. The synthetic process route of using acrylic acid and alkylene oxide as raw materials to synthesize hydroxyalkyl acrylate is reasonable and feasible, and the research focus of this process route is to develop efficient catalysts. Yin Jiazi and Zhu Xinbao experimentally verified catalysts such as chromium catalysts, iron catalysts and organic amines in the literature, but various catalysts have their own advantages and disadvantages. After studying the hydroxyalkyl acrylate synthesized by these catalysts, it was found that when used in the synthesis of concrete admixtures, the hydroxyalkyl acrylate needs to be purified, otherwise the residual catalyst will have a certain negative impact on the synthesis of concrete admixtures. Summary of the invention

[0007] The invention aims to provide a quaternary ammonium salt catalyst, wherein the quaternary ammonium salt prepared by the reaction of hexamethylenetetramine and ethylene iodide is used as a catalyst for the synthesis of hydroxyalkyl olefinate, and the preparation method is simple.

[0008] The purpose of the present invention is to provide an environmentally friendly method for synthesizing hydroxyalkyl acrylates that can be directly used in the synthesis of polycarboxylic acid concrete admixtures. The quaternary ammonium salt prepared by the reaction of hexamethylenetetramine and vinyl iodide is used as a catalyst to prepare hydroxyalkyl acrylates, which has high catalytic efficiency, good selectivity, no need for material separation, and is environmentally friendly. The prepared hydroxyalkyl acrylates can be directly used in the synthesis of polycarboxylic acid concrete admixtures.

[0009] Another object of the present invention is to provide an application of an environmentally friendly hydroxyalkyl acrylate that can be directly used in the synthesis of a polycarboxylic acid concrete admixture, for the synthesis of a polycarboxylic acid concrete admixture.

[0010] The specific technical solutions of the present invention are as follows:

[0011] The present invention provides a quaternary ammonium salt catalyst, the structural formula of which is

[0012] The preparation method of the quaternary ammonium salt catalyst is:

[0013] Weigh hexamethylenetetramine and dissolve it in chloroform. Add vinyl iodide to react under heating and pressure conditions. Purify after the reaction is completed.

[0014] The mass ratio of hexamethylenetetramine to chloroform is 1:(2.0-5.0);

[0015] In the preparation method of the quaternary ammonium salt catalyst, the heating and pressurizing conditions refer to a reaction temperature of 40-80° C., a reaction pressure of 0.1-1.0 MPa, and a reaction time of 1.0-3.0 h.

[0016] The molar ratio of hexamethylenetetramine to vinyl iodide is 1:(1.0-1.2);

[0017] The synthesis of the quaternary ammonium salt catalyst of the present invention comprises the following steps: after the catalyst synthesis is completed, nitrogen is used to purge and remove chloroform at 60° C. to obtain quaternary ammonium salt catalyst crystals without further purification.

[0018] The purity of the hexamethylenetetramine is above 99%, the purity of the vinyl iodide is above 80%, and the purity of the chloroform is above 99%.

[0019] The reaction equation of the quaternary ammonium salt catalyst is:

[0020]

[0021] The present invention provides an environmentally friendly method for synthesizing hydroxyalkyl acrylate that can be directly used in the synthesis of polycarboxylic acid concrete admixtures, specifically comprising:

[0022] The quaternary ammonium salt catalyst, polymerization inhibitor and acrylic acid prepared above are mixed, and alkylene oxide is introduced into the mixture under heating and pressurizing conditions in a protective atmosphere for reaction, and the mixture is kept warm for aging. After the reaction is completed, the mixture is cooled and discharged.

[0023] The quaternary ammonium salt catalyst is used in an amount of 5‰-20‰ of the mass of acrylic acid;

[0024] The amount of the polymerization inhibitor is 0.5‰-10‰ of the mass of acrylic acid;

[0025] The effective content of the quaternary ammonium salt catalyst is ≥ 90%;

[0026] The molar ratio of acrylic acid to alkylene oxide is 1:(1.0-2.0);

[0027] The acrylic acid has a purity of ≥99.5%;

[0028] The alkylene oxide has a water content of ≤1000ppm, a gas phase purity of ≥99%, and an aldehyde content of ≤100ppm, and the alkylene oxide includes one of ethylene oxide (EO for short) and propylene oxide (PO for short);

[0029] The inhibitor is one of hydroquinone, tert-butylcatechol, phenothiazine, diethylhydroxylamine, and 4-hydroxy-2,2,6,6-tetramethylpiperidinyl nitroxide free radical. Acrylic acid is an organic acid containing unsaturated double bonds, which has high activity and is easy to self-polymerize in the presence of a catalyst. A certain amount of inhibitor needs to be added, which can also prevent the self-polymerization of hydroxyalkyl acrylate.

[0030] The protective atmosphere is nitrogen;

[0031] The heating and pressurizing conditions refer to a reaction temperature of 50-150°C and a reaction pressure of 0.1-1.0MPa;

[0032] The heat preservation and aging means that after the introduction of alkylene oxide is completed, the heat preservation reaction time is 1.0h.

[0033] The synthesis of the cycloalkyl acrylate mainly refers to hydroxyethyl acrylate (HEA for short) and hydroxypropyl acrylate (HPA for short);

[0034] Preferably, the synthesis method of the environmentally friendly hydroxyalkyl acrylate that can be directly used in the synthesis of polycarboxylic acid concrete admixtures is:

[0035] Add quaternary ammonium salt catalyst, polymerization inhibitor and acrylic acid into the reactor, seal the reactor and replace with nitrogen three times, heat the reactor to the set temperature, and introduce alkylene oxide into the reactor at 50-150° C. and a reaction pressure of 0.1-1.0 MPa. After the feeding is completed, continue to keep warm and mature. After the reaction is completed, cool to below 50° C. and discharge to obtain a reaction liquid of hydroxyalkyl acrylate.

[0036] The environmentally friendly hydroxyalkyl acrylate prepared by the above method and directly used in the synthesis of polycarboxylic acid concrete admixtures has the following structural formula:

[0037] Wherein R is one of H or CH3.

[0038] The reaction equation for the synthesis of environmentally friendly hydroxyalkyl acrylate that can be directly used in the synthesis of polycarboxylic acid concrete admixtures is:

[0039] R is one of H or CH3.

[0040] The present invention provides an environmentally friendly hydroxyalkyl acrylate that can be directly used for the synthesis of polycarboxylic acid concrete admixtures. It can be directly used for preparing polycarboxylic acid concrete admixtures without purification.

[0041] The structural formula of the polycarboxylic acid concrete admixture is:

[0042] Wherein R is one of H or CH3; a is a positive integer between 1 and 20; b is a positive integer between 20 and 80; c is a positive integer between 10 and 30; n is a positive integer between 50 and 70;

[0043] The preparation method of the polycarboxylic acid series concrete admixture specifically comprises: using polyether macromonomer, oxidant and water as primer materials, preparing an aqueous solution of acrylic acid and environmentally friendly hydroxyalkyl acrylate which can be directly used for the synthesis of polycarboxylic acid series concrete admixture as dropwise addition material A, a reducing agent and a chain transfer agent as dropwise addition material B, and preparing an alkali solution as dropwise addition material C; dropwise adding material A, material B and material C into the primer material; and after the dropwise addition is completed, heat-insulating the reaction.

[0044] The structural formula of the polyether macromonomer is:

[0045] Wherein n is a positive integer between 50 and 70; the polyether macromonomer is selected from vinyl polyoxyethylene ether;

[0046] The preparation method of the polycarboxylic acid concrete admixture is carried out at room temperature and normal pressure.

[0047] The mass ratio of the polyether macromonomer, acrylic acid and environmentally friendly hydroxyalkyl acrylate that can be directly used for the synthesis of polycarboxylic acid concrete admixture is 30: (0.6-3.0): (1.5-5);

[0048] In the preparation method of the polycarboxylic acid concrete admixture, the mass concentration of material A is 50%;

[0049] The dropping time of material A was 1.0 h, the dropping time of material B was 1.0 h, and the dropping time of material C was 1.5 h. After the dropping was completed, the heat preservation reaction time was 1.0 h.

[0050] The oxidant is one of hydrogen peroxide, sodium persulfate and ammonium persulfate, and the amount used is 0.1%-5% of the mass of the polyether macromonomer.

[0051] The reducing agent is one of L-ascorbic acid, Rongalite and sodium formaldehyde sulfoxylate, and the amount used is 0.1%-1% of the mass of the polyether macromonomer.

[0052] The chain transfer agent is one of mercaptoethanol, mercaptopropanol, thioglycolic acid, mercaptopropionic acid, and sodium hypophosphite, and the amount used is 0.2%-1% of the mass of the polyether macromonomer;

[0053] The alkali solution is one of sodium hydroxide solution and potassium hydroxide solution, and the mass concentration is 10%; the usage amount is 1%-5% of the mass of the polyether macromonomer.

[0054] The polycarboxylic acid concrete admixture of the present invention is prepared by polymerization of vinyl polyoxyethylene ether macromonomer, acrylic acid and self-made hydroxyalkyl acrylate; the free radical polymerization method is an aqueous phase free radical polymerization method, and the initiation system includes an oxidant, a reducing agent and a chain transfer agent.

[0055] The catalysts mentioned in the existing ring-opening method show excellent catalytic activity and selectivity for the synthesis of hydroxyalkyl acrylates, but there are also some problems and shortcomings. At present, the catalysts used in the industrialization of hydroxyalkyl acrylates are mainly chromium catalysts. The main problem is that the subsequent purification process is troublesome, and the hydroxyalkyl acrylate is prone to self-polymerization during purification. If the purification process is not carried out, the residual chromium will have a certain impact on the synthesis of polycarboxylic acid concrete admixtures. And chromium ions are heavy metal ions, which are harmful to the environment.

[0056] Compared with the prior art, the present invention adopts quaternary ammonium salt synthesized by vinyl iodide and hexamethylenetetramine as catalyst, which is used for preparing hydroxyalkyl acrylate, has fast reaction speed, high conversion rate, and can be directly used for the synthesis of concrete admixture without subsequent purification treatment. Due to the characteristics of environmental protection, high efficiency and direct use in the synthesis of concrete admixture, it is particularly suitable for industrial production. The catalyst structure of the present invention contains alkene groups, which not only has no effect on the ring opening of alkylene oxide. And because a double bond is introduced into hexamethylenetetramine to form a quaternary ammonium salt catalyst, when synthesizing polycarboxylic acid, the double bond in the catalyst will break and undergo water-phase free radical polymerization with polyether macromonomer, acrylic acid, hydroxyalkyl acrylate, etc., to generate a comb-shaped polycarboxylic acid structure, which not only has no negative impact on the synthesis of polycarboxylic acid concrete admixture, but also becomes a kind of polycarboxylic acid, and the performance of polycarboxylic acid concrete admixture is further improved. After the double bond is introduced into hexamethylenetetramine, a quaternary ammonium salt catalyst is formed. Since the catalyst contains a double bond, the double bond can be disconnected to undergo aqueous phase free radical polymerization with polyether macromonomers, acrylic acid, hydroxyalkyl acrylate, etc., to form a polycarboxylic acid structure, which is similar to the admixture structure and also has a promoting effect on concrete performance. In practical applications, this method can significantly reduce production costs, improve production efficiency, and simultaneously ensure the quality and performance of the product. The environmentally friendly synthesis method of the present invention will be more popular in the market. Through the implementation of the present invention, not only the progress of hydroxyalkyl acrylate synthesis technology can be promoted, but also the green development and sustainable development of the concrete admixture industry can be promoted. Therefore, the present invention has a wide range of industrial applicability in the fields of chemical synthesis, concrete admixture production, etc. The catalyst described in the present invention does not contain toxic and harmful substances such as heavy metals, is an environmentally friendly catalyst, and will not pollute the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is the GPC data spectrum of the product of Example 3;

[0058] Figure 2 This is the GPC data spectrum of the product in Example 6. DETAILED DESCRIPTION

[0059] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0061] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0062] The number average molecular weight Mn, weight average molecular weight Mw, molecular weight distribution (Mw / Mn) and polymer peak area ratio of the present invention are determined by Waters e 2695 gel permeation chromatograph. (Mobile phase: 0.1 mol / L NaNO3 aqueous solution; mobile phase speed: 0.6 ml / min; injection volume: 30 μl; sample preparation concentration: 2% (sample g / mobile phase g);

[0063] The reaction solution of the hydroxyalkyl acrylate of the present invention is tested by Shimadzu 2030 gas chromatograph, the chromatographic column is Agilent HP-5 chromatographic column (column length × column inner diameter × coating thickness: 30m × 0.32mm × 0.25um), and the sample is tested by injection of ethanol solution with a mass ratio of 1:10. The test conditions are: the injection volume is 0.2 microliters, the split ratio is 20:1, the injection port temperature is set to 250°C, the detector temperature is set to 270°C, and the column oven is set to program temperature rise (initial 100°C, hold 1min, 5°C / min to 160°C, hold 1min, 20°C / min to 200°C, hold 6min, 10°C / min to 260°C, hold 5min).

[0064] Example 1

[0065] A preparation method of a quaternary ammonium salt catalyst comprises the following steps: 100 g of hexamethylenetetramine is weighed and dissolved in 200 g of chloroform, and the mixture is pumped into a reaction kettle under vacuum negative pressure conditions, and then the mixture is reacted with vinyl iodide at a molar ratio of 1:1 for 2 hours at a temperature of 80° C. and a pressure of 0.5 MPa to generate hexamethylenetetramine salt. After the reaction is completed, chloroform is removed by purging with nitrogen at 60° C. to obtain quaternary ammonium salt catalyst crystals without further purification.

[0066] Example 2

[0067] The invention discloses an environmentally friendly method for synthesizing hydroxyalkyl acrylate which can be directly used for the synthesis of polycarboxylic acid concrete admixtures. Specifically, 600g of acrylic acid, 5.0g of quaternary ammonium salt catalyst prepared in Example 1 and 0.5g of phenothiazine as a polymerization inhibitor are weighed and added to a reactor, and the reactor is sealed and nitrogen replaced three times. The reactor is heated to 100°C, the feed amount of ethylene oxide (EO for short) is 400g, the feed time is controlled to be about 2h, the reaction temperature is controlled to be 100±5°C, and the maximum reaction pressure is 0.5MPa. After the feed is completed, the heat preservation reaction is continued for 1.0h to obtain a brown-yellow hydroxyethyl acrylate reaction liquid, and a sample is taken for GC test (area normalization method / %): ethylene oxide 2.26%, acrylic acid 0.42%, diethylene glycol monoacrylate 5.74%, ethylene glycol diacrylate 0.03%, hydroxyethyl acrylate 91.27%, and other unknown components 0.28%.

[0068] Example 3

[0069] The environmentally friendly hydroxyalkyl acrylate prepared in Example 2, which can be directly used in the synthesis of polycarboxylic acid concrete admixtures, is used in the synthesis of polycarboxylic acid concrete admixtures:

[0070] Weigh 360g of vinyl polyoxyethylene ether with a molecular weight of 2400, add water to prepare a 60% aqueous solution, and add 2.0g of hydrogen peroxide; weigh 30.0g of acrylic acid and 20.0g of the prepared hydroxyethyl acrylate to prepare a 50% aqueous solution as material A; weigh 1.5g of reducing agent Rongalite and 3.0g of chain transfer agent mercaptopropionic acid to prepare a 10% aqueous solution as material B; prepare 40g of 10% sodium hydroxide lye as material C for dripping. Start dripping the above A, B, and C materials into the bottom material at the same time according to the time of 1h, 1h, and 1.5h respectively. After the dripping is completed, mature for 1h. The structural formula of polycarboxylic acid water reducer is:

[0071]

[0072] Detect the GPC data of polycarboxylate water reducer, such as Figure 1 The GPC conversion rate was 96.18%, Mn=22591, Mw=39400, Mw:Mn=1.744.

[0073] According to the standard GB / T8077-2000 experimental method, the difference in the fluidity of the pure slurry is measured: △FL0=5mm, △FL 60 =7mm, △FL 120 =6mm.

[0074] Example 4

[0075] Weigh 150g of hexamethylenetetramine and dissolve it in 300g of chloroform. Pump it into the reactor under vacuum and negative pressure. Then, react it with vinyl iodide at a molar ratio of 1:1.1 at 60°C and a reaction pressure of 0.6MPa for 1.5h to generate a quaternary ammonium salt catalyst (hexamethylenetetramine salt). After the reaction is completed, remove the solvent chloroform under nitrogen protection, and the hexamethylenetetramine salt will precipitate in the form of a crystalline salt without further purification.

[0076] Example 5

[0077] Weigh 500g of acrylic acid, 8.0g of the catalyst prepared in Example 4, and 0.8g of hydroquinone into the reactor, seal the reactor and replace with nitrogen three times. The reactor is heated to 80°C. The feed amount of propylene oxide (PO for short) is 400g, the feed time is controlled to about 2h, the reaction temperature is controlled to 80±5°C, and the maximum reaction pressure is 0.4MPa. After the feeding is completed, the reaction is kept warm for 1.0h to obtain a brown-yellow hydroxyethyl acrylate reaction liquid, and samples are taken for GC testing (area normalization method / %): propylene oxide 1.44%, acrylic acid 0.65%, 1,3-propylene glycol monoacrylate 6.52%, 1,3-propylene glycol diacrylate 0.06%, hydroxypropyl acrylate 90.82%, and other unknown components 0.51%.

[0078] Example 6

[0079] Weigh 360g of vinyl polyoxyethylene ether with a molecular weight of 2400 and configure it into a 60% aqueous solution, add 2.8g of hydrogen peroxide; weigh 36.0g of acrylic acid and 26.0g of the prepared hydroxypropyl acrylate and configure it into a 50% aqueous solution as material A; weigh 2.0g of reducing agent Rongalite and 2.8g of chain transfer agent mercaptoethanol and configure it into a 10% aqueous solution as material B; configure 45g of 10% sodium hydroxide lye as material C for dripping. Start dripping the above A, B, and C materials into the bottom material at the same time according to the time of 1h, 1h, and 1.5h respectively. After the dripping is completed, mature for 1h. The structural formula of the polycarboxylic acid water reducer is obtained:

[0080]

[0081] The GPC data of polycarboxylate water reducer was tested. The GPC conversion rate was 96.28%, Mn = 23961, Mw = 45225, Mw:Mn = 1.887. The GPC data spectrum is as follows Figure 2 .

[0082] According to the standard GB / T8077-2000 experimental method, the difference in fluidity of the pure slurry is measured: △FL0 = -4mm, △FL 60 =8mm, △FL 120=8mm.

[0083] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A quaternary ammonium salt catalyst, characterized in that The structural formula of the quaternary ammonium salt catalyst is 2. The quaternary ammonium salt catalyst according to claim 1, characterized in that The preparation method of the quaternary ammonium salt catalyst is: Weigh hexamethylenetetramine and dissolve it in chloroform. Add vinyl iodide to react under heating and pressure conditions. Purify after the reaction is completed.

3. The quaternary ammonium salt catalyst according to claim 2, characterized in that In the preparation method of the quaternary ammonium salt catalyst, the heating and pressurizing conditions refer to a reaction temperature of 40-80° C., a reaction pressure of 0.1-1.0 MPa, and a reaction time of 1.0-3.0 h.

4. The quaternary ammonium salt catalyst according to claim 2, characterized in that The molar ratio of hexamethylenetetramine to vinyl iodide is 1:(1.0-1.2).

5. A method for synthesizing an environmentally friendly hydroxyalkyl acrylate that can be directly used in the synthesis of polycarboxylic acid concrete admixtures, characterized in that: The synthesis method uses the quaternary ammonium salt catalyst of claim 1 as a catalyst, and the synthesis method comprises: mixing the quaternary ammonium salt catalyst, a polymerization inhibitor and acrylic acid, introducing alkylene oxide to react under a protective atmosphere and under heating and pressurizing conditions, keeping the temperature for aging, and cooling and discharging the material after the reaction is completed.

6. The synthesis method according to claim 5, characterized in that The amount of the quaternary ammonium salt catalyst used is 5‰-20‰ of the mass of acrylic acid.

7. The synthesis method according to claim 5, characterized in that The molar ratio of acrylic acid to alkylene oxide is 1:(1.0-2.0).

8. The synthesis method according to claim 5, characterized in that The dosage of the polymerization inhibitor is 0.5‰-10‰ of the mass of acrylic acid.

9. The synthesis method according to claim 5 or 8, characterized in that: The polymerization inhibitor is one of hydroquinone, tert-butylcatechol, phenothiazine, diethylhydroxylamine, and 4-hydroxy-2,2,6,6-tetramethylpiperidinyl nitroxide free radical.

10. The synthesis method according to claim 5 or 8, characterized in that: The heating and pressurizing conditions refer to a reaction temperature of 50-150° C. and a reaction pressure of 0.1-1.0 MPa.

11. An application of an environmentally friendly hydroxyalkyl acrylate synthesized by the synthesis method according to any one of claims 5 to 10 and directly used for the synthesis of polycarboxylic acid concrete admixtures, characterized in that: It can be directly used to prepare polycarboxylic acid concrete admixtures.

Citation Information

Patent Citations

  • Method for preparing polyether for polycarboxylic acid series concrete additive

    CN101164957A

  • Slow-release slump-retaining type polycarboxylic acid high-performance water reducing agent and preparation method thereof

    CN104692700A

  • Anti-mud-type polycarboxylic-acid water-reducing agent and preparation method thereof

    CN105800992A

  • Preparation method of vinasse synergistic polycarboxylate superplasticizer

    CN112062915A

  • Quaternary ammonium salt polymer and preparation method thereof

    CN113929809A